The Case of Lisbon Treaty; An Elitist Analysis of the State of Democracy in the EU - Goga, Aida (Richtmann Publishing, 2013)
The gap separating elite and popular opinion on the path and finality of the European Union was never as visible as it becameafter the negative referendums on the Constitutional Treaty followed by the introduction of Lisbon Treaty. This paper tries toanalyse this issue in the light of an elitist theory and it is organized as follows: In the first section the problem will becharacterized by means of some theoretical considerations. The following section discusses the key facts from the birth of theConstitution to the birth of the Lisbon Treaty. It is followed by some facts that show that the Lisbon Treaty maintains almost thesame content as the rejected Constitution, concluding with some final observations. In more specific terms, this essay willfocus on the introduction of Lisbon Treaty after the failure of the European Constitution in the referenda during 2005. Therelevant dynamic is not the formulation of a Treaty per se but the important dynamic that will be discussed relates to theparticularities that associate this specific Treaty. The analysis of the introduction of Lisbon Treaty will be under the light of anelitist conception of democracy which constitutes the theoretical framework of the paper. The direct link between the theoreticalbasis and the Lisbon Treaty as a case study is the process of transition -from the failure of the European Constitution derivedby a referenda -to a new â€œimposedâ€ Treaty that substantially maintains the same content.According to this approach, democracy in the EU can be seen mainly as a means to change the governing elites and not asthe rule of the â€œpeopleâ€. In relation to this, Lisbon Treaty is just a subsequent elitist project sharpening further the gap betweenâ€œpeopleâ€ and the ruling elites.